ANALISIS RENDAHNYA KEMAMPUAN BERPIKIR KRITIS SISWA INDONESIA BERDASARKAN PERSPEKTIF TEORI BELAJAR KOGNITIF DALAM SISTEM PEMBELAJARAN MODERN - Natasha Aditya Putri; M. Mamduh Winangun; Sri Usodoningtyas (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article discusses the problem of low critical thinking skills among students in Indonesia in a modern learning context. This can be seen from global data and field reports which show that many students tend to rely on rote memorization rather than systematically analyzing and evaluating information. The aim of this article is to examine this problem through a cognitivism theory approach and formulate alternative solutions that are appropriate to the educational context in Indonesia. The method used is a literature review using secondary data, including reports on education, PISA data, and a national scientific journal as the main reference. The learning theory chosen is cognitivism, with an emphasis on cognitive development according to Piaget, the zone of proximal development by Vygotsky, as well as the principles of learning based on discovery and information processing. The results of the analysis show that low critical thinking skills are closely related to the mismatch between students' cognitive stages, the dominance of passive learning by rote memorization, and an assessment system that still focuses on results. This article recommends the application of a problem-based learning model, collaboration in discussion, and assessment that pays attention to the process as the main solution to improve students' critical thinking skills using a cognitivism theory approach.